Covid Anxiety and Immune System (International Journal of Ayurveda and Pharma Research, 2022)
In the era of global transmission, when all the luxurious concept stands meaningless people are forced to believe the concept of ‘individualistic approach in disease management’. This pandemic COVID 19 has been an eye opener which showed the world that there doesn’t exists any magic pill. The one and only protector we have is our immune system. Many people are prone to ill health due to their irregular dietary habit (Āharaja), activities (Vihāraja) change in climate, on the other hand, some people remain healthy in spite of violating healthy rules and do not get affected by any disease. This is because of the variation in their immune power. Ayurveda described Vyādhikşhamatva in more detail and magnificent way which can be considered equivalent to modern concepts of immunity. The term Vyādhikşhamatva is made up of two words; Vyādhi (disease) and kşhamatva (suppress or overcome). Ayurveda describes numerous health practices as Dinacarya, Ritucarya, Rasāyana, Sadvritta, Acāra rasāyana, Yoga and meditation to help mind and body to thrive. Homeostasis of Ojas, Agni, Srotas, Doşa and Duşya along with and associated is the pleasant state of sensory organs and mind, soul essential for good health. The government interventions during COVID-19 like Punarjani, Sukhayushyam, Swasthyam, Niramaya, Ayur raksha clinics which aims at strengthening the preventive mechanism gives Ayurveda a new ray of hope to globalize its importance.